Women and the Transformation of Batik Culture in Pemusiran, East Tanjung Jabung, Jambi - Saipul Saipul; Amirudin Amirudin; Adrian Wibisono; Ahmad Ramadlan (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2021)
This study examines the role of women in transforming the Pemusiran Batik culture through a partnership with the private agency Petrochina Tanjung Jabung Jambi. The research uses the perspective of the diffusion of innovations Everett M. Rogers (1964) which explains that cultural transformation through the process of diffusion of innovation requires the role of actors as agents of change. This study uses an action research method in which the researcher together with the actor Suraedah as a female character, conducts an assessment and transforms the Pamusiran batik culture. The study was carried out for 4 months from January 1, 2021 to April 30, 2021. The study found that, as the earliest actor in adopting innovation, Suraedah played an important role in the transformation of the cultural innovation of Pemusiran batik. The transformation process occurs in the diffusion of innovations starting from: (1) studying innovations, adopting, and developing social networks through the